Prevajalci-kleriki in translatio studii v srednjeveški Franciji - Vaupot, Sonia (Bogoslovni vestnik, 2025)
The article examines the role of cleric translators in the transmission of knowledge and power in medieval France, drawing on the concepts of transla-tio studii and translatio imperii. By translating various texts, these translators adapted knowledge into Middle French while serving the interests of both ecclesiastical and royal institutions. The study highlights the ideological and political stakes of these translations, as well as the resistance they encounte-red. It analyses the role of various patrons, particularly Charles V, in promotingtranslation as a tool of governance and knowledge unification. Finally, it traces the evolution of these practices until the end of the Middle Ages, when tran-slation became a key instrument for the dissemination of knowledge, marking the transition towards humanism.
Keywords: cerkveno prevajanje; cleric translators; ecclesiastical translation; medieval translation; prevajalci-kleriki; prevajanje v srednjem veku; tran-slatio imperii; translatio im-perii; translatio studii